2011
DOI: 10.3171/2010.3.jns097
|View full text |Cite
|
Sign up to set email alerts
|

Counterbalancing risks and gains from extended resections in malignant glioma surgery: a supplemental analysis from the randomized 5-aminolevulinic acid glioma resection study

Abstract: Extended resections performed using a tool such as 5-ALA-derived tumor fluorescence, carries the risk of temporary impairment of neurological function. However, risks are higher in patients with deficits unresponsive to steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
173
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(182 citation statements)
references
References 13 publications
4
173
0
5
Order By: Relevance
“…One of the greatest barriers to achieving optimal surgical results in infiltrative tumors is the difficulty in distinguishing tumor from normal brain (5)(6)(7). Failure to discern where the border of the lesion ends and viable, minimally infiltrated brain begins increases the likelihood of inadequate resection and neurological damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the greatest barriers to achieving optimal surgical results in infiltrative tumors is the difficulty in distinguishing tumor from normal brain (5)(6)(7). Failure to discern where the border of the lesion ends and viable, minimally infiltrated brain begins increases the likelihood of inadequate resection and neurological damage.…”
mentioning
confidence: 99%
“…Although maximal surgical resection with the goal of gross total tumor resection is desirable, in practice, delineation of resection margins is difficult because tumors can closely resemble healthy brain, often infiltrate brain tissue, and may be immediately adjacent to critical functional brain tissue. Aggressive resection can increase the risk for postoperative neurological deficits (7). For example, brain tumors located near critical brain areas subserving primary motor, sensory, or language functions are difficult to resect maximally while avoiding postoperative neurological deficits (8).…”
mentioning
confidence: 99%
“…Alternatively, 5‐aminolevulinic acid (5‐ALA), a bio‐precursor of protoporphyrin IX (PPIX), has gained considerable attentions in recent years, and PDT with ALA‐derived endogenous porphyrins has already shown promising clinical results in the treatment of several superficial disorders of the skin (such as actinic keratosis, a skin condition that will further develop into cancer) and internal hollow organs 5. 5‐ALA is an endogenous amino acid, which is usually synthesized from glycine and succinyl CoA in mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…21,34,43 Similarly, post hoc analysis of the 5-ALA study 41 showed a 4.9-month survival difference between patients who underwent gross-total resection (GTR) and those who underwent STR, even though the difference in residual tumor volume was marginal (0 vs 0.7 cm 3 for GTR and STR, respectively). 42 Delivering an optimal oncological result in patients with tumors adjacent to motor eloquent areas thus requires the ability to resect tumor tissue down to very low MTs (1-2 mA).…”
Section: The Need For Refinement Of Mapping Techniquementioning
confidence: 99%